Adding dynamicity to consumer value dimensions: An exploratory approach to intrinsic values and value outcomes in the hotel industry. Issue 2 (20th January 2020) - Sánchez-Fernández, Raquel; Gallarza, Martina G.; Arteaga, Francisco
Abstract : Purpose: The purpose of this paper is to examine the dynamic nature of consumer value by proposing a causal model that shows the existence of sequentiality in value dimensions and in their influence on satisfaction and loyalty. The paper focuses on intrinsic dimensions of value (play, aesthetics, ethics and escapism), which are fully experiential, and therefore less studied in the literature. Design/methodology/approach: The conceptual model proposed was empirically tested in tourist hotel accommodations. Data were collected through a structured questionnaire, analyzing the experiences of 285 hotel guests with structural equation modeling-partial least squares. Findings: The results reveal that the reactive dimensions of value (aesthetics and escapism) influence the active ones (play and ethics), which in turn affect consumers' satisfaction and loyalty. Research limitations/implications: This paper is exploratory and focuses on the intrinsic dimensions of value. Future research should consider the entire extrinsic/intrinsic value duality. This paper is based on a convenience sample consisting solely of hotel accommodation. Further studies based on a random sample and on other hospitality contexts would be required to generalize the results. Practical implications: This paper can help hotel managers to understand the role and importance of each intrinsic dimension of value to successfully implement their relationship marketing strategies, defined by the chain value-satisfaction-loyalty. Originality/value: This paper depicts the dynamic nature of value, with concatenated (and not simultaneous) effects of value dimensions on satisfaction and loyalty, which supports research in value co-creation.